1996
DOI: 10.1021/ja962491m
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Bis(2,2‘-bipyridyl)platinum(I):  A Novel Microtubular Linear-Chain Complex

Abstract: One-electron reduction of [Pt(bpy)2]2+ (bpy = 2,2‘-bipyridyl) in aqueous solution results in the formation of black-green lustrous needles on solid electrodes. The crystalline needles grow perpendicularly from the substrate surface and reach lengths of 1−2 cm. Elemental analysis, X-ray photoelectron spectroscopy, and electrochemical measurements indicate that the new compound is a genuine PtI complex with a d9 electronic configuration and with the composition [Pt(bpy)2]NO3·2H2O. X-ray crystallographic analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“…23,24 A single report exists of a monomeric Pt(I) complex, namely [(bipy) 2 Pt] + (bipy = 2,2 0 -bipyridyl). 25 Although it contains potentially redox non-innocent bipyridine ligands, the original experimental evidence and our calculations 26 agree on the Pt(I) assignment ( Figure S7). Monomeric Pd(I) complexes have been proposed as intermediates in some reactions of Pd(0) complexes with alkyl halides as early as the 1970s 27 and more recently in reactions of Pd(0) complexes…”
Section: Introductionsupporting
confidence: 74%
“…23,24 A single report exists of a monomeric Pt(I) complex, namely [(bipy) 2 Pt] + (bipy = 2,2 0 -bipyridyl). 25 Although it contains potentially redox non-innocent bipyridine ligands, the original experimental evidence and our calculations 26 agree on the Pt(I) assignment ( Figure S7). Monomeric Pd(I) complexes have been proposed as intermediates in some reactions of Pd(0) complexes with alkyl halides as early as the 1970s 27 and more recently in reactions of Pd(0) complexes…”
Section: Introductionsupporting
confidence: 74%
“…Nevertheless, a number of [Pt(bpy) 2 ] 2+ salts have been prepared and structurally characterized and the ways in which the complexes adapt to minimise the steric interactions are of considerable interest. In some cases, the electronic demands of the bpy ligand to maximize conjugation in a planar conformation dominates and the geometry of the PtN 4 motif in the [Pt(bpy) 2 ] 2+ cation is distorted towards tetrahedral, with least squares planes angles between the near-planar bpy ligands between 30 and 37° (Figure 19a) [171,172,173]. In other cases, the electronic preference of the d 8 metal centre for a square-planar PtN 4 motif dominates, and the bpy adopts a V-shaped conformation about the interannular C–C bond (Figure 19b) [174,175,176,177,178,179].…”
Section: 1930–1939—golden Years and Then Back Into The Abyssmentioning
confidence: 99%
“…13). In the earlier studies, relatively simple models (28)(29)(30)(31) were developed and their photo-hydrogen-evolving activities were tested [22,37]. However, it was found that these compounds do not preserve the important photochemical properties required to enhance the visible-light-induced charge separation process: the strong electronic coupling between the Ru(bpy) 3 2+ -like moiety and the heavy Pt ion promotes the quenching of the 3 MLCT excited state of the Ru(bpy) 3 2+ -like moiety [26].…”
Section: Development Of Photo-hydrogen-evolving Molecular Devicesmentioning
confidence: 99%